Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1038/s41598-020-80484-x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and purification of glycoglycerolipids to induce apoptosis in breast cancer cells

Abstract: Monogalactosyldiacylglycerol (MGDG) is the most abundant type of glycoglycerolipid found in the plant cell membrane and mostly in the chloroplast thylakoid membrane. The amphiphilic nature of MGDG is attractive in pharmaceutical fields for interaction with other biological molecules and hence exerting therapeutic anti-cancer, anti-viral, and anti-inflammatory activities. In this study, we investigated the therapeutic efficacy of cyanobacteria derived MGDG to inhibit breast cancer cell growth. MGDG was extracte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…ITC-induced inhibition of Hh pathway and promotion of cell apoptosis was verified by the increase in caspase-3 level of the tumors in different groups ( Figure 7(B) ). Caspase-3, an apoptotic biomarker, is activated in response to chemotherapy and is considered a significant indicator for treatment efficacy in breast cancer (Abedin & Barua, 2021 ). The level of caspase-3 in tumors of all treated groups was significantly higher relative to untreated control.…”
Section: Resultsmentioning
confidence: 99%
“…ITC-induced inhibition of Hh pathway and promotion of cell apoptosis was verified by the increase in caspase-3 level of the tumors in different groups ( Figure 7(B) ). Caspase-3, an apoptotic biomarker, is activated in response to chemotherapy and is considered a significant indicator for treatment efficacy in breast cancer (Abedin & Barua, 2021 ). The level of caspase-3 in tumors of all treated groups was significantly higher relative to untreated control.…”
Section: Resultsmentioning
confidence: 99%
“…Cancer cells can proliferate without limit. One of the most important features of an effective anticancer drug is the control of cancer cell progression and induction of apoptosis as required ( Abedin and Barua, 2021 ). Extensive biochemical analysis revealed that EF40 arrests NSLCL cells in the G2/M phase in response to ROS-induced DNA damage and ultimately triggers apoptosis, probably due to the failure of DNA repair ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…All together, these data suggest that the anti-proliferative effect may be associated with the presence of the glycoglycerolipid compound (monogalactosyl-monoacylglycerol, MGMG, 18:3; at m / z 277.2174) detected in the extracts from all vegetables. Previously, it has been reported that the monogalactosyldiacylglycerol (MGDG), another type of glycoglycerolipid found in the plant cell membrane, showed therapeutic anti-cancer activity [ 38 ]. The different levels of anti-proliferative activity observed in this study may be associated with the other compounds present in the different extracts.…”
Section: Discussionmentioning
confidence: 99%